2010
DOI: 10.1104/pp.110.160044
|View full text |Cite
|
Sign up to set email alerts
|

A Fertilization-Independent Developmental Program Triggers Partial Fruit Development and Senescence Processes in Pistils of Arabidopsis

Abstract: The pistil is the specialized plant organ that enables appropriate pollination and ovule fertilization, after which it undergoes growth and differentiation to become a fruit. However, in most species, if ovules are not fertilized around anthesis the pistil irreversibly loses its growth capacity. We used physiological, molecular, and transcriptomic tools to characterize the postanthesis development of the unfertilized Arabidopsis (Arabidopsis thaliana) pistil. Surprisingly, developmental processes that have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 57 publications
7
78
0
3
Order By: Relevance
“…S6E), consistent with a general down-regulation of ethylene-related expression after anthesis (Vriezen et al, 2008;Wang et al, 2009). Pollination is known to induce a burst of ethylene in tomato ovaries accompanied by a transient increase in ACO gene expression (Llop-Tous et al, 2000), and it has been suggested that ethylene is involved in controlling ovule senescence and the fruit-set response (Carbonell-Bejerano et al, 2010). By spatially resolving gene expression, our data implicate the ovule as a likely site of ethylene biosynthesis in ovaries, with specific ACO isoforms, such as ACO4 (Fig.…”
Section: A Map Of Hormone-related Gene Expression During Early Fruit mentioning
confidence: 69%
“…S6E), consistent with a general down-regulation of ethylene-related expression after anthesis (Vriezen et al, 2008;Wang et al, 2009). Pollination is known to induce a burst of ethylene in tomato ovaries accompanied by a transient increase in ACO gene expression (Llop-Tous et al, 2000), and it has been suggested that ethylene is involved in controlling ovule senescence and the fruit-set response (Carbonell-Bejerano et al, 2010). By spatially resolving gene expression, our data implicate the ovule as a likely site of ethylene biosynthesis in ovaries, with specific ACO isoforms, such as ACO4 (Fig.…”
Section: A Map Of Hormone-related Gene Expression During Early Fruit mentioning
confidence: 69%
“…The level of 18S rRNA was measured as an internal standard (Izumi et al, 2012). The gene-specific primers were used in previous studies (Baena-González et al, 2007;Carbonell-Bejerano et al, 2010;Izumi et al, 2012;Maruta et al, 2012;Ramel et al, 2012;Shao et al, 2013;Wang and Blumwald, 2014). The sequences of primers for qRT-PCR analysis are shown in Supplemental Table 1.…”
Section: Qrt-pcrmentioning
confidence: 99%
“…In addition to their importance in controlling cell death in the transmitting tract, HAF, BEE1 and BEE3 also influence cell death in the stigma (Carbonell-Bejerano et al, 2010). Stigmatic cells degenerate soon after pollination in wild type, but remain intact in haf bee1 bee3 mutants even 7 days post-anthesis.…”
Section: Research Articlementioning
confidence: 99%
“…It seemed possible that delayed cell death in mutant stigmata might prolong pollen receptivity (Carbonell-Bejerano et al, 2010). Wild-type carpels have been reported to be receptive to pollination and fertilization for up to 4 days after the flower has opened at anthesis (Vivian-Smith et al, 2001).…”
Section: Research Articlementioning
confidence: 99%